Ekonomiczność innowacji składniowych w kontekście normy językowej - Ewa Kołodziejek (Postscriptum Polonistyczne)
The author analyses contemporary syntactic innovations based on usus, but incorrect according to linguistic rules, such as: odnośnie czego, przed i po obiedzie, dwa lub więcej samochodów, szampon dla zdrowych włosów. She proves that such forms result from language economy and the level of their preservation leads to the possibility of their normative acceptance.